Patterns of Activity in the Human Frontal and Parietal Cortex Differentiate Large and Small Saccades - Grosbras, Marie-Hélène (Frontiers in Integrative Neuroscience, 2016)
A vast literature indicates that small and large saccades, respectively, subserve different perceptual and cognitive strategies and may rely on different programming modes. While it is well established that in monkeys’ main oculomotor brain regions small and large eye movements are controlled by segregated neuronal populations, the representation of saccade amplitude in the human brain remains unclear. To address this question we used functional magnetic resonance imaging (fMRI) to scan participants while they performed saccades towards targets at either short (4 degrees) or large (30 degrees) eccentricity. A regional multivoxel pattern analysis (MVPA) reveals that patterns of activity in the frontal (FEF) and parietal eye fields discriminate between the execution of large or small saccades. This was not the case in the supplementary eye fields nor in the inferior precentral cortex. These findings provide the first evidence of a representation of saccadic eye movement size in the fronto-parietal occulomotor circuit. They shed light on the respective roles of the different cortical oculomotor regions with respect to space perception and exploration, as well as on the homology of eye movement control between human and non-human primates.